Sensitivity to Thyroid Hormones and Risk of Prediabetes: A Cross-Sectional Study - Liu, Bingyang; Wang, Zixiao; Fu, Jinrong; Guan, Haixia; Lyu, Zhaohui; Wang, Wei (Frontiers in Endocrinology, 2021)
Context: Thyroid hormone influences glucose homeostasis through both central and peripheral regulation. However, the association of sensitivity to thyroid hormones with prediabetes remained unknown. We aimed to investigate the association between sensitivity to thyroid hormones and risk of prediabetes in the general and euthyroid population. Methods: Participants with serum free triiodothyronine (FT3), free thyroxine (FT4) and thyrotropin (TSH) measurements from the health checkup programs of the First Hospital of China Medical University were enrolled. We calculated parameters representing central and peripheral sensitivity to thyroid hormones (central sensitivity, assessed by calculating Thyroid Feedback Quantile-based Index (TFQI), TSH Index (TSHI), and Thyrotroph Thyroxine Resistance Index (TT4RI); peripheral sensitivity, evaluated by FT3/FT4 ratio). Associations of sensitivity to thyroid hormones with risk of prediabetes were assessed with logistic regression. Results: A total of 4378 participants (mean age±SD, 49±11 years) were included, with 1457 (33%) subjects had prediabetes. The risk of prediabetes was negatively associated with levels of TSHI (odds ratio [OR] 0.91; 95% confidence interval [CI], 0.85-0.97), TT4RI (OR 0.91; 95% CI, 0.84-0.99) and Parametric TFQI (PTFQI) (OR 0.89; 95% CI, 0.83-0.95) among all subjects. The association remained significant in euthyroid subjects and euthyroid subjects with negative thyroid autoimmunity. Higher FT3/FT4 ratio was associated with a mild increased risk of prediabetes (95% CI 1.09; 1.02-1.16). Compared with subjects in the lowest quartile of PTFQI, those in the highest quartile had lower risk of prediabetes (0.70; 95% CI, 0.58-0.84). Conclusions: Decreased central sensitivity to thyroid hormones is associated with lower risk of prediabetes. This demonstrates the complex interaction of thyroid system with glucose metabolism, while future studies are warranted to confirm our findings and underlying mechanisms.